Duration of treatment among patients prescribed afatinib or erlotinib as first-line therapy for EGFR mutation-positive non-small-cell lung cancer in the USA. (19th March 2019) - Lim, Jonathan; Samuelsen, Carl; Golembesky, Amanda; Shrestha, Sulena; Wang, Li; Griebsch, Ingolf
Aim: Evaluate duration of therapy among patients treated with afatinib or erlotinib as first-line therapy for non-small-cell lung cancer (NSCLC).Materials & methods: NSCLC patients initiating afatinib or erlotinib between 2014 and 2017 were identified in three large claims databases in the USA. Propensity score matching was conducted to compare the duration of treatment between patients by treatment.Results: Patients prescribed afatinib had a significantly longer median duration of treatment compared with those prescribed erlotinib (12.1 vs 9.9 months; p = 0.035) and experienced a 14% reduction in risk of discontinuing therapy (adjusted hazard ratio: 0.86; CI: 0.75–0.99).Conclusion: First-line treatment duration in a real-world setting was significantly longer for patients prescribed afatinib compared with erlotinib.